Unveiling the impact of interferon genes on the immune microenvironment of triple-negative breast cancer: identification of therapeutic targets - Liu, Ying; Cai, Jiayi; Fahira, Aamir; Zhuang, Kai; Wang, Jiaojiao; Zhang, Zhi; Yan, Lin; Liu, Yong; Ouyang, Defang; Huang, Zunnan (Frontiers in Bioinformatics, 2025)
ObjectiveTriple-negative breast cancer (TNBC), a classic subtype of breast cancer, is challenging to treat due to the lack of drug-targeting receptors. This study aims to explore interferon-related prognostic molecular biomarkers in TNBC and their potential competing endogenous RNA (ceRNA) regulatory network in TNBC.MethodsRNA expression profiles and interferon genes were downloaded from the Cancer Genome Atlas (TCGA) database and the Gene Set Enrichment Analysis (GSEA) website, respectively. Univariate and multivariate Cox regression analyses were performed to identify prognostic genes and construct a risk model. Single-sample GSEA (ssGSEA) and the CellMiner database were used to explore the relationships between prognostic genes and both tumor immune microenvironment and drug sensitivity, respectively. The lncRNA-miRNA-mRNA network associated with prognosis was constructed using the ENCORI database. Finally, the potential interferon-associated lncRNA/miRNA/mRNA regulatory axis was identified through correlation analysis. The abnormal expressions of prognostic genes were validated in three TNBC tumor cell lines compared to normal mammary epithelial cells by using quantitative real-time polymerase chain reaction (qRT-PCR).ResultsThe TNBC prognostic signature comprising four interferon genes (STXBP1, LAMP3, CD276, and POLR2F) was identified, with their expression significantly correlated with the infiltration abundance of multiple immune cells and the drug sensitivity of 30 diverse drugs (ARQ-680, Fluphenazine, and Chelerythrine, etc.). Furthermore, an interferon-related genes prognostic ceRNA network was further constructed, consisting of 248 lncRNAs, 66 miRNAs, and 4 mRNAs. As a result, 5 interferon-related ceRNA regulatory axes (AC124067.4/hsa-miR-455-3p/STXBP1, RBPMS-AS1/hsa-miR-455-3p/STXBP1, DNMBP-AS1/hsa-miR-455-3p/STXBP1, FAM198B-AS1/hsa-miR-455-3p/STXBP1, LIFR-AS1/hsa-miR-455-3p/STXBP1) associated with TNBC progression were identified. QRT-PCR results showed that all four prognostic mRNAs were upregulated in TNBC cells.ConclusionThis study established a prognostic signature and a ceRNA network associated with interferon in TNBC, and identified five key regulatory axes. In the prognostic signature and the ceRNA axes, STXBP1, RBPMS-AS1, and FAM198B-AS1 were first reported as potential biomarkers of TNBC. These findings have the potential to provide new insights into the mechanisms driving TNBC tumorigenesis and development.